Evolution of the RNA polymerase II C-terminal domain - Stiller, John W.; Hall, Benjamin D. (East Carolina University, 2002)
In recent years a great deal of biochemical and genetic research has focused on the C-terminal domain (CTD) of the largest subunit (RPB1) of DNA-dependent RNA polymerase II. This strongly conserved domain of tandemly repeated heptapeptides has been linked functionally to important steps in the initiation and processing of mRNA transcripts in both animals and fungi. Although they are absolutely required for viability in these organisms, C-terminal tandem repeats do not occur in RPB1 sequences from diverse eukaryotic taxa. Here we present phylogenetic analyses of RPB1 sequences showing that canonical CTD heptads are strongly conserved in only a subset of eukaryotic groups, all apparently descended from a single common ancestor. Moreover, eukaryotic groups in which the most complex patterns of ontogenetic development occur are descended from this CTD-containing ancestor. Consistent with the results of genetic and biochemical investigations of CTD function, these analyses suggest that the enhanced control over RNA polymerase II transcription conveyed by acquired CTD protein interactions was an important step in the evolution of intricate patterns of gene expression that are a hallmark of large, developmentally complex eukaryotic organisms. Originally published Proc Natl Acad Sci, Vol. 99, No. 9, Apr 2002
Keywords: Development; RPB1; Transcription